A review of recent progress toward the efficient separation of circulating tumor cells via micro‐/nanostructured microfluidic chips. Issue 1 (31st January 2022) - Liu, Xiaoshi; Ma, Liang; Yan, Wenyuan; Aazmi, Abdellah; Fang, Minghe; Xu, Xiuzhen; Kang, Hanyue; Xu, Xiaobin
Abstract: Circulating tumor cells (CTCs) are closely correlated with cancer diagnoses, and their early detection can help patients receive accurate prognoses in a noninvasive manner. However, the rarity, fragility, and heterogeneity of CTCs introduce significant technical challenges to their separation from blood. Recent advances in micro‐/nanofabrication techniques have made microfluidic chips better for CTC separation. In this review, we mainly focus on recent progress made in the development of microfluidic chips incorporating micro‐/nanostructures for the CTC separation. Specifically, we reviewed two major CTC separation mechanisms, that is, physical and chemical approaches. Representative works on physical mechanism‐based approaches (include pillar filtration, cross‐flow filtration, deterministic lateral displacement, smart materials, and bionics); immunomagnetic beads, and surface modification; and chemical mechanism‐based approaches include diversity of affinity ligand selection, are reviewed. Their advantages and disadvantages are compared and discussed, and a perspective on the future direction of CTC is provided. Abstract : Circulating tumor cells (CTCs) are closely correlated with cancer diagnoses, and their early detection can help patients receive accurate prognoses in a noninvasive manner. Recent advances in micro‐/nanofabrication techniques have made microfluidic chips better for CTC separation. Recent progress made in the development of microfluidic chips incorporating micro‐/nanostructures, and their major separation mechanisms, including physical and chemical, are provided in this review.